2019
DOI: 10.3390/en12010133
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Effect of Tunnel Aspect Ratio on Evacuation with Unsteady Heat Release Rate Due to Fire in the Case of Two Vehicles

Abstract: In this study, the characteristics of fires in case of two vehicles in a tunnel are analyzed by Computational Fluid Dynamics analysis for varying tunnel aspect ratios. Unsteady heat release rates over time are set as the input conditions of fire sources considering real phenomena. Unsteady heat release rate values are obtained from experiments. As a result, the smoke velocities above the fire source appear faster in the case of tunnels with a large aspect ratio because the higher the height of the tunnel, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Applying the actual heat release rates obtained from this study to the numerical analysis study, Park et al published a study on the effect of a vehicle accident on the evacuation in various tunnel aspect ratio [27]. The maximum heat release values obtained by other studies are shown in Table 4 and compared with the results obtained through this experiment.…”
Section: Heat Release Ratementioning
confidence: 90%
“…Applying the actual heat release rates obtained from this study to the numerical analysis study, Park et al published a study on the effect of a vehicle accident on the evacuation in various tunnel aspect ratio [27]. The maximum heat release values obtained by other studies are shown in Table 4 and compared with the results obtained through this experiment.…”
Section: Heat Release Ratementioning
confidence: 90%
“…When the merging ratio is equal to 0.4, the stairs evacuation capacity is optimal. In general, 0.5 is regarded as the optimal merging ratio [2], but the pedestrian output rate of the oor platform is calculated by the pedestrian number of oor platforms. Appropriately increasing the width of the stairs or decreases the width of the oor channel can improve the pedestrian output rate of the oor platform.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Every pedestrian possesses independent movement characteristics; (2) e stairs pedestrian merging obeys a Poisson distribution; (3) e density of pedestrians can in uence the merging process; (4) e stairs evacuation adopts the FCFS (First Come First Served) involved in the scheduling theory.…”
Section: Calculation Of Pedestrian Output Rate Of Floor Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of recent multiscale modeling approaches for tunnel fire modeling is presented in the study by Ralph and Carvel [27]. Recently, research regarding the tunnel aspect ratio has been studied by experiments [28] and by modeling [29].…”
Section: Introductionmentioning
confidence: 99%